2006
DOI: 10.4049/jimmunol.177.12.8484
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Stress Enhances Susceptibility of Murine Adult Offspring toward Airway Inflammation

Abstract: Allergic asthma is one of the most prevalent and continuously increasing diseases in developed countries. Its clinical features include airway hyperresponsiveness and inflammation upon allergen contact. Furthermore, an emerging area of research subsumed as fetal programming evaluates the impact of environmental insults in utero on the incidence of diseases in later life. The aim of this study was to identify whether prenatal exposure to stress, which constitutes a severe environmental insult, perpetuates airwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
96
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(102 citation statements)
references
References 38 publications
5
96
1
Order By: Relevance
“…Evidence in rhesus monkeys links prenatal stress to antigen-induced responses at birth (22). Dysregulated immune response to antigen challenge has also been demonstrated in prenatally stressed adult mice, reflected by an enhanced Th2 adaptive response (23).…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
“…Evidence in rhesus monkeys links prenatal stress to antigen-induced responses at birth (22). Dysregulated immune response to antigen challenge has also been demonstrated in prenatally stressed adult mice, reflected by an enhanced Th2 adaptive response (23).…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
“…Sound stress, which is widely used in neuro-endocrine-immunological research [3,5,20,21], has been demonstrated to induce neurogenic skin inflammation in mice [4,22] and the premature termination of murine hair growth [2,4]. Blockade of the neurokinin-1 receptor [2], for which SP has the highest affinity, as well as neutralization of NGF abrogate stress-induced neurogenic inflammation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies suggest effects begin prenatally. Prenatal stress increases allergen-induced airway inflammation (10,11) and airway hyperesponsiveness (12) in mice offspring and impacts the newborn's antigen response in primates (13). Although no prospective human study has measured prenatal maternal stress directly in association with wheeze or other early asthma phenotypes in children, three have considered maternal psychologic functioning as a correlate of stress exposure.…”
mentioning
confidence: 99%